An Introduction to the Theology of Fandom, with Emphasis on the Iranian Fans of the Exo Korean Music Band - Mohammad Javad Badinfekr (پژوهشنامه فلسفه دین, 2022)
Assuming that practical theology seeks to think in a theological way about the individual and collective human being act, it is vital to heed one of the modern and theological forms of modern culture, namely the theology of fandom. The historical roots of fandom theology must be traced back to pre-modern and traditional times. In this article, we explain the ritual behaviors of modern fans using Paul Tillich's theoretical approach to the theology of culture. One of the obvious differences between modern, media-based fandom and fandom in traditional culture is the relationship between the fan and the celebrity through the media text, contrary to the traditional model in which the physical presence of the fan and the guide was used to be the main principle for the formation of the relationship. In this article, we will explain some of the features of fandom theology in modern culture. Moreover, we attempt to point out what are the differences between modern fans and traditional fans by presenting samples such as the behaviors of Iranian fans for one of the Korean pop bands. We also criticize the modern secular theology of fandom which is in contrast with traditional monotheistic one. In addition, the relation between the fans of Korean band Exo and religious matter will be investigated.